Research regarding taraxacum officinale (L.) weber with the intention of therapeutic exploring. Note I. studies of phenolcarboxylic acids - Stylianou, Natela; Gekas, Vassilis; Istudor, Viorica; Ioniţǎ, Corina Ana (My University, 2014)
The current study was intended to evaluate the accumulation of the cichoric acid (dicaffeoyltartaric acid) in Taraxacum officinale (L.) Weber (dandelion) in relation to the harvesting time and determination of an adequate method of extraction, required to obtain a pharmacological-active extract, standardized in cichoric acid, necessary for elaboration of a pharmaceutical product used in the therapy of the metabolic diseases. The plant material was harvested from wild flora (from Limassol - Cyprus) in all vegetation phases. The extraction method (Ultrasound Assisted Extraction = UAE/maceration) and the solvent (ethanol 70%) were selected based on determination of the cichoric acid by high pressure liquid chromatography coupled with UV (HPLC/UV), the method selected from the scientific literature and optimized by the authors. The highest amount of cichoric acid was found in leaves before the flowering phase, in March (51.77 mg/g) and in the roots after the flowering period, in December (4.89 mg/g) using the ultrasound. For flowers, fruits and stems the values were between 3.19 mg/g - 5.06 mg/g. The optimized method was adequate for the proposed objective The quantitative determination revealed a considerable quantity of cichoric acid in the plant, for that reason the dandelion can be considered as a potential source of cichoric acid.
Keywords: Cichoric acid; HPLC/UV; Taraxacum officinale; Ultrasound assisted extraction